Intervensi latihan keterampilan motorik kasar pada fungsi kognitif anak usia prasekolah - Khasana, Tri Mei; Inayah, Inayah (Jurnal Gizi Klinik Indonesia, 2024)
Gross motor skills training on cognitive function in early primary schoolBackground: Low gross motor skills are associated with low physical activity in preschool and elementary school children. Children's gross motor skills are correlated with obesity and contribute to physical activity participation and physical, social, and cognitive growth.Objective: This study aims to determine the effect of gross motor skills training intervention on the cognitive function of early elementary school children.Methods: A quasi-experimental study with a one-group pretest-posttest with a control design. The study involved first-year children from two elementary schools in Pleret, Bantul, DIY, with a total of 90 participants (49 boys, 41 girls) and a mean age of 7 years. The intervention consisted of motor skills training, including obstacle courses and walking on a balance beam, with each session lasting 15 minutes and conducted once a week for nine weeks. Cognitive function in terms of memory and attention abilities was assessed using the Stroop test (Stroop color and word test) and the digit span test (forward and backward)—data analysis using paired sample t-test and independent sample t-test.Results: The study's results indicated a significant difference in the mean scores of the Stroop test for both the intervention and control groups and the digit span test for the intervention group. The findings suggested that motor skills training intervention significantly positively affected children's cognitive function, particularly with the Stroop test.Conclusions: Gross motor skill training can enhance the cognitive function of children aged 6-7. Motor skill instruction should be incorporated into preschool and early elementary school programs to help narrow the academic achievement gap.